Digital-Based Flash Card to Increase Social Studies Learning Outcomes for Elementary School Students in The Fourth Grade - Ajat Sudrajat; Fhadya Giaani Salsabila; Arita Marini (Universitas Pendidikan Ganesha, 2023)
The development of innovative learning media is needed to provide a different and varied learning experience. This is required to stimulate student interest in learning to achieve maximum learning outcomes. The aim of this study is to develop and analyze the effect of digital-based flashcard media to improve social studies learning outcomes for fourth-grade elementary school students. This research uses R&D (Research and Development) methods and adapts the ADDIE development model. The population in this study were fourth-grade students. This study randomly took a sample of 126 fourth-grade students and calculated using the Slovin formula with a margin of error of 5%. The results of this study show that the results of material expert validation 83.3% in the worthy category. The results of media experts 93.3% in the very worthy category, and the results of the effectiveness of learning media are obtained through a questionnaire given to students at the pretest and posttest. This study concludes that digital-based flashcard media positively impacts social studies learning outcomes for fourth-grade elementary school students.